Influence of eccentric strength of knee extensor muscles on biomechanical factors of a vertical drop jump - Oh, J.; Lee, H.-D. (Journal of Electromyography and Kinesiology, 2022)
During a vertical drop jump (VDJ), the human neuromuscular system absorbs and reuses external loads applied to the lower extremity by coordinating the musculoskeletal system. This study aims to investigate the influence of the eccentric strength of the knee extensor muscles on the biomechanical factors of a VDJ. Participants were divided into two groups based on the eccentric strength of their knee extension muscles: low eccentric (LECC) and high eccentric (HECC) strength groups. The VDJ joint kinematics and kinetics of the lower extremity, the fascicle behavior of the vastus lateralis, and the muscle activation of the knee extensor muscles were simultaneously recorded during maximum-effort VDJ. Compared with the LECC group, the HECC group showed a higher jump, greater knee and ankle joint stiffness, and smaller fascicle length change. These findings suggest that the eccentric strength capacity of the knee extensor muscles accounts for the different biomechanical strategies (bouncing-type for HECC and absorbing-type for LECC) observed between the groups. Consequently, the eccentric strength of the knee extensor muscle may be an essential factor in determining the biomechanical strategy for VDJ and should be considered in the jumping performance enhancement training paradigm.